White boys, white noise : masculinities and 1980s indie guitar rock - Bannister, Matthew (Ashgate popular and folk music series., 2006)
Through textual analysis of musical and critical discourses, Bannister provides the first book-length study of masculinity and ethnicity within the context of indie guitar music within US, UK and New Zealand 'scenes'. Drawing on his own experience as an indie musician, Bannister surveys a range of indie artists, demonstrating broad continuities between these apparently disparate scenes, in terms of gender, aesthetic theory and approaches to popular musical history. The result is a book which raises some important questions about how gender is studied in popular culture and the degree to which.